Developing an ICT blueprint for a mid-size build-to-order corporation - Christian Gläser (2016)
Structuring and documenting the IT landscape is increasingly important for IT management. By giving an example for a mid-size built-to-order corporation, a formal and documented ICT blueprint is created based on an informal reference model. The implementation uses Enterprise Architecture Methods and considers integration aspects. The thesis also illustrates the dependencies between Business-, Enterprise- and IT-Architecture and evaluates the current state of research regarding mass customization, Enterprise Architecture Management and integration frameworks with a focus on service-oriented architecture (SOA).